2009
DOI: 10.1086/597527
|View full text |Cite
|
Sign up to set email alerts
|

Hindgut Plasticity in Wallabies Fed Hay either Unchopped or Ground and Pelleted: Fiber Is Not the Only Factor

Abstract: Phenotypic plasticity of the gastrointestinal tract is crucial for optimal food processing and nutrient balance in many vertebrate species. For mammalian herbivores, gut plasticity is typically correlated with the fiber content of forage; however, we show here that other factors such as ingesta particle size may effect profound phenotypic plasticity of the fermentative hind-gut in a medium-sized (10-kg body mass) marsupial herbivore, the red-necked wallaby (Macropus rufogriseus). When dietary fiber contents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The results of this study corroborate previous evidence (Langer et al 1980;Schwarm et al 2009b) that, in contrast to common expectations (Hume 1999, p. 240;Munn and Dawson 2006;Lentle et al 2007;Munn et al 2007), the forestomach of macropods does not appear to differentiate the passage of differently-sized particles. On the one hand, it has been suggested that, similar to the large intestine of rabbits, the macropod forestomach eliminates large particles faster than small particles (Hume 1999, p. 240).…”
Section: Lack Of Particle-size Differentiation In the Macropod Forestsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study corroborate previous evidence (Langer et al 1980;Schwarm et al 2009b) that, in contrast to common expectations (Hume 1999, p. 240;Munn and Dawson 2006;Lentle et al 2007;Munn et al 2007), the forestomach of macropods does not appear to differentiate the passage of differently-sized particles. On the one hand, it has been suggested that, similar to the large intestine of rabbits, the macropod forestomach eliminates large particles faster than small particles (Hume 1999, p. 240).…”
Section: Lack Of Particle-size Differentiation In the Macropod Forestsupporting
confidence: 89%
“…In macropods, a differential passage of different sized particles has been suspected (Hume 1999). In tammar wallabies, the proportion of small particles in the forestomach decreases with time since feeding (Lentle et al 2007), and in both tammar wallabies and red-necked wallabies (Macropus rufogriseus), a finely-ground diet increased the material present in the caecum and colon, suggesting that fine particles pass through the forestomach quicker and accumulate in the hindgut Munn et al 2007). These findings could suggest a selective expulsion of fine particles from the macropod forestomach.…”
Section: Introductionmentioning
confidence: 94%
“…The results for the pygmy hippos, babyrousa and wild boar are also given in Table 1. The large intestine wet content mass of the monogastric hindgut-fermenting suid, the wild boar, was (1968), Presbytis cristatus, leaf monkey, Pí (1973) and Kay et al (1976), Colobus polykomos, Western black and white colobus monkey, Hume (1977) and Munn et al (2009) Macropus rufogriseus, rednecked wallaby, Warner (1981) and Munn et al (2006) Macropus eugenii, Tammar wallaby, Dellow and Hume (1982) …”
Section: Resultsmentioning
confidence: 99%
“…Nutritional physiology encompasses more than a simple accounting of the foodstuffs that are available at a release site, and potentially considers a wide range of factors that are relevant to translocations. These factors include the phenotypic plasticity of the gastrointestinal system ( Starck, 1999a , b , 2005 ; Millán et al , 2003 ; O'Regan and Kitchener, 2005 ; Starck and Wang, 2005 ; Munn et al , 2006 , 2009 ), the impacts of gut pathogens ( Everest, 2007 ), microbes or other intestinal symbionts that are needed for healthy digestion ( Hooper and Gordon, 2001 ; Kohl and Dearing, 2012 ), and microbial ‘seeding’ of captive-reared animals, particularly herbivores, to aid digestion following release, and even foraging behaviours; all of these factors can ultimately affect survival and breeding success.…”
Section: Physiology and Conservation Translocationmentioning
confidence: 99%